Architecture for a semantic repository of research documents - Uribe Gómez, Gustavo Andrés; Álvarez Sánchez, Pedro Harvey (I+ T+ C- Research, Technology and Science, 2017)
Due the need to facilitate the information recovery in the research context, the improvement of the precision and recall in repositories of research documents is needed. The Semantic Web is a promising set of technologies for that, including languages to describe taxonomies and ontologies. Thus, through of this article A Methodology Associated Bliss New Technology Presented : Generic Component Model, which is allows you to create information systems that are developed from ontologies much richer in : semantic elements, a situation that allows better search Associated Information Research. This model is characterized by describing the system allowing graininess